Waveguide fabrication in KDP crystals with femtosecond laser pulses - Huang, L; Salter, P; Karpiński, M; Smith, B; Payne, F; Booth, M (Springer Berlin Heidelberg, 2015)
Optical waveguides fabricated in potassium dihydrogen phosphate (KDP) by ultrafast laser pulses are demonstrated. Dependent on the incident pulse energy, two different types of refractive index modification have been induced. For moderate laser powers, type I homogeneous waveguides are created. At higher pulse energies, type II waveguides are formed in the stressed area surrounding regions of laser-induced damage. Double-line and four-line structures are applied to the type II guides to increase mode confinement. Polarization sensitivity and transmission properties of the written waveguides are characterized and discussed. The results indicate that high-quality waveguides can be fabricated in KDP, which has potential for further applications in nonlinear integrated-optics.